A Model for Adapting Evidence-Based Interventions to Be LGBQ-Affirmative: Putting Minority Stress Principles and Case Conceptualization Into Clinical Research and Practice. Issue 1 (February 2023) - Pachankis, John E.; Soulliard, Zachary A.; Morris, Faithlynn; Seager van Dyk, Ilana
Highlights: This adaptation model reduces barriers to implementing LGBQ-affirmative practice. The model provides a tool for implementing clinical trial results in practice. LGBQ-affirmative principles provide evidence-based clinical guidance. Systematic LGBQ-affirmative case conceptualization ensures flexible yet yet targeted uptake. Abstract: The mental health field now possesses clinical trials attesting to the efficacy of affirmative practice with sexual minority individuals. With the goal of efficiently moving the results of these clinical trials into real-world clinical practice, this paper offers a model for adapting existing evidence-based practices originally developed for the general population to be lesbian, gay, bisexual, and queer (LGBQ)-affirmative. The adaptation model presented here guides clinicians to incorporate six LGBQ-affirmative transtheoretical principles of change into practice. These principles facilitate raising awareness of the impact of minority stress on sexual minority clients' mental health and on client self-evaluation while drawing upon sexual minority resilience and intersectional experiences to build empowering coping skills and validating relationships. The adaptation model also provides a transtheoretical approach to case conceptualization that directs clinicians to consider the role of early and ongoing minority stress on sexual minority clients' cognitive, affective, motivational, behavioral, and self-evaluative experiences that maintain current distress. This case conceptualization approach highlights common associations among these experiences, suggesting clear routes of interventions for many sexual minority client presentations. Case examples from recent clinical trials of LGBQ-affirmative cognitive-behavioral therapy illustrate how these principles and this case conceptualization can be effectively utilized in practice. While the principles and case conceptualization are meant to be transtheoretical and therefore applicable across therapeutic techniques, to date they have been tested only in clinical trials for cognitive-behavioral treatments. Therefore, this paper concludes with a call for future research to determine the effectiveness of implementing this adaptation model across diverse therapeutic modalities and client presentations.